Ternate Cinnamon Flour Supplementation (Cinnamomum spp.) in Ration on Internal Organ Phenotype, First Egg-Laying Age, and Quality of Quail Eggs (Coturnix coturnix japonica) - Sri Utami; Sariffudin Fatmona (Postgraduate, University of Mataram, 2025)
This study aimed to evaluate the effect of supplementation of Ternate cinnamon flour (Cinnamomum spp.) in rations on internal organ phenotypes, age of first egg-laying and quality of Japanese quail eggs (Coturnix coturnix japonica). A total of 192 two-week-old female quails were used with a complete random design (RAL) consisting of four treatments and four replicates, 12 each per replication, for a total of 192 quails. The treatment provided included a control ration without cinnamon flour (P0), supplementation of 1% (P1), 2% (P2), and 3% (P3). The parameters observed included liver weight, spleen weight, age of first egg, egg index, egg weight, and shellwork thickness. The results showed that cinnamon flour supplementation had a significant effect (P < 0.05) on liver weight, age of first egging, and egg shell quality. A 2% cinnamon flour (P2) treatment provides the best results with normal internal organs, faster egg-laying life, and optimal egg quality. Thus, cinnamon flour supplementation can be a natural strategy to improve the productivity and reproductive health of Japanese quails.